Epigenetic Dynamics: Role of Epimarks and Underlying Machinery in Plants Exposed to Abiotic Stress - Manoj Kumar Dhar; Parivartan Vishal; Rahul Sharma; Sanjana Kaul (International Journal of Genomics)
Abiotic stress induces several changes in plants at physiological and molecular level. Plants have evolved regulatory mechanisms guided towards establishment of stress tolerance in which epigenetic modifications play a pivotal role. We provide examples of gene expression changes that are brought about by conversion of active chromatin to silent heterochromatin and vice versa. Methylation of CG sites and specific modification of histone tail determine whether a particular locus is transcriptionally active or silent. We present a lucid review of epigenetic machinery and epigenetic alterations involving DNA methylation, histone tail modifications, chromatin remodeling, and RNA directed epigenetic changes.